Intellectual Capital and Performance of Indonesian Islamic Banks: A Maqasid Sharia Perspective - Purwanti, Winaya; Safrudin, Safrudin; Saifudin, Asep; Gustiawan, Deni (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine how intellectual capital (IC) affects Islamic general banks' maqashid sharia performance from 2018 to 2022. The components of IC, namely Human Capital (IB-VAHU), Capital Employed (IB-VACA), and Structural Capital (IB-STVA), are the three independent variables under investigation. This study employs a secondary quantitative research design, as determined by Econometric Views (E-Views) version 12's panel data linear regression approach. The study's participants are Islamic Commercial Banks registered with the Financial Services Authority (OJK). With a sample size of 11 businesses, the sample was chosen using the purposive sampling technique, making a total of 13 banks included in the study. Secondary data was employed in this investigation. The data collection process uses the documentation method accessed via each Islamic commercial bank's official website. The study's findings show the positive relationship between human capital and maqashid sharia performance; the higher a company's human capital, the better its maqashid sharia performance. Capital Employed has no bearing on how well Maqashid Sharia works. The performance of maqashid sharia is negatively impacted by structural capital; the coefficient value, which is pointing in the negative direction, shows that the more human capital a corporation has, the lower its maqashid sharia performance.